การพัฒนาแนวทางการก่อตั้งโรงเรียนศิลปะการเต้น - วัลลภา ปัจฉิมสวัสดิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The purposes of this research were to: 1) develop the guidelines to establish a dance school, and 2) study the desirable characteristics of the school. The research framework investigated the Private School Act B.E. 2550 and research guidelines on how to establish a school. The research sample comprised school administrators, teachers, students, and parents of dance schools in the Bangkok area. Five-point Likert scale questionnaires and a focus group were used to collect the data. Percentage, mean, standard deviation, and content analysis were used to analyze all data. The research findings were as follows: 1) School Establishing Guidelines based on government rules and regulations. Data filed upon these rules and regulations should be derived from a customers’ needs survey. Data include school principals, school administration, and the desirable characteristics of a school. 2) The desirable characteristics of a school were: 1) School focus – the focus on student ability at a level high enough to pursue his/her dancing career; 2) School academic affairs – use the Basic Education Core Curriculum while utilizing learning development activities and additional courses/activities provided by schools, depending on their readiness and priorities in the area of dance; 3) Student recruitment – use a dance exam as the main entrance exam; 4) Teachers – use psychology of learning along with the art of teaching, 5) School operation fee – start from 5,000,000 baht for a small-size school with a student body of 60; and 6) School fee – start from 100,000 baht per year for a small-size school as well.